Kontribusi Pajak Daerah Terhadap Produk Domestik Regional Bruto Kabupaten Bolaang Mongondow Selatan - Syawaluddin, Syawaluddin; Safitri, Rina (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2021)
Local taxes are taxes whose management and collection are carried out by local governments and for the benefit of the region itself as well as a source of regional income that contributes to the Gross Regional Domestic Product (PDRB). Gross regional domestic product (GRDP) is one of the macroeconomic indicators designed to present economic events in the exploitation of these resources and further understand the relationship between the transactions that occur in between. In Bolaang Mongondow Selatan Regency, the increase in Regional Original Income (PAD) is dominated by the contribution of tax revenues and levies. Local taxes and levies are the largest revenues that can contribute to the South Bolaang Mongondow Regional Original Revenue. Local taxes are able to become a mainstay in contributing to GRDP, because it is in line with the rapid development and economy in Bolaang Mongondow Selatan Regency. The purpose of this study was to determine the contribution of local taxes to the Gross Regional Domestic Product (PDRB) of Bolaang Mongondow Selatan Regency. This research is a quantitative study using secondary data (time series) in the 2010-2020 observation period. PDRB data collection is obtained from BPS South Bolaang Mongondow Regency, while regional tax and PAD data are obtained from South Bolaang Mongondow BPKPD. The results obtained are approximately 62.3% of local taxes have a significant effect on contributing to the Gross Regional Domestic Product (GRDP).